Women's International League for Peace and Freedom At Courthouse Transit Stop Protesting Removal From Buses Their "Think Before You Register For The Draft" Signs - Watkins, Howard::::::::: (1982)
Protesters getting off of City bus at City Hall stop carrying banned posters and many wearing poster words on T-shirts; Evo Bluestein, Nancy Marsh and Sandy Iyall on left side; Cindy Calvert, Lindell Cross, Barbara Gaines,? and Louise Erickson bottom right; Ernestine Leas exiting bus